Gender trouble : - Butler, Judith (Routledge, 2006)
Arguing that traditional feminism is wrong to look to a natural, 'essential' notion of the female, or indeed of sex or gender, Butler starts by questioning the category 'woman' and continues in this vein with examinations of 'the masculine' and 'the feminine'. Best known however, but also most often misinterpreted, is Butler's concept of gender as a reiterated social performance rather than the expression of a prior reality.